Livelihood struggles and market reform: (un)making Chinese labour after state socialism - Ching Kwan Lee (United Nations Research Institute for Social Development (UNRISD), 2005)
The surge of China as the workshop of the world has been founded on, among other things, a fundamental restructuring of the labour force. Massive unemployment in the state industrial sector is taking place simultaneously with momentous migration of peasants into global factories. Both the unmaking and the making of the Chinese working class are heavily shaped by the state. This paper traces the historical evolution of core changes in Chinese labour reform and worker entitlements: from the introduction of labour contracts to the promulgation of a national labour law, the demolition of work-unit socialism and its replacement with a national social security system. I also examine workers' livelihood struggles in response to this epochal transformation. The central problem for Chinese workers is not the new labour and welfare systems, but the wide discrepancies between the stipulation and the implementation of these new policies. The institutional source of these gaps, this paper argues, lies in two contradictions inherent in the strategy of Chinese reform. Firstly, the imperative to rely on local accumulation to fuel marketization clashes with the imperative to maintain legitimacy by providing a basic level of justice and welfare for the most disadvantaged. Local state agents are more interested in the former than the latter, especially when they can count on central government financial intervention to maintain social stability. The second contradiction in Chinese reform that is conducive to uneven protection of labour rights has to do with the illiberal nature of the Chinese legal system. The state uses the law as a means of controlling society, while allowing itself to remain mostly unrestrained by the law. When it is not in the interest of the local officials to enforce labour regulations, there is hardly enough countervailing authority-from the judiciary, for instance-to preserve the sanctity of the law. The result is that many workers, on seeing their legal rights and entitlements unjustly denied, and pressured by livelihood needs, become politically restive. Sharp increases of labour conflicts are accompanied by proliferation of labour activism, taking both conventional (that is, petition, labour arbitration and litigation) and unconventional (that is, protests, marches and road blockage) forms. The state has responded with measured mixes of concessions and repression. Economic and livelihood demands are recognized and, in many cases, at least partially answered by swift financial compensation doled out by the central or provincial governments. On the other hand, political demands such as those relating to the removal of officials and cross-factory actions are relentlessly suppressed and harshly punished. Protests notwithstanding, the Chinese Government has ardently pressed ahead with social security reform, targeting problem areas such as pension arrears, unpaid wages, unemployment benefits and medical insurance. Additional, earmarked funds are funneled from Beijing to provincial coffers to deal with social grievances that may erupt into social instability. There are also plans to systematically institutionalize the provision of legal aid to people who fall below a particular income level. Therefore, the Chinese state has responded to popular demands, if only slowly and selectively. Finally, both migrant workers and state workers are not totally dispossessed or proletarianized. Rural land rights for peasant migrants and private home ownership for state sector workers have functioned as safety valves to sooth the effects of massive unemployment and diabolical exploitation. Women in the two segments of the working-class examined here do face gender-specific difficulties. The disappearance of enterprise-based welfare means more demands put on the family unit to provide service and financial support. These domestic burdens are still borne predominantly by women. Also, women are among the first to be let go when enterprises restructure by down-sizing the workforce. Facing gendered disadvantages in the labour market, and under a welfare-entitlement regime based on employment rather than universal citizenship, female workers are likely to fall through the cracks of the new social safety net. The male bias in socialist allocation of housing in the past has inadvertently undermined women's opportunities to become homeowners when work units began privatizing welfare housing in the reform period. For young female migrants toiling in global factories, the lack of maternity benefits forces them to truncate their factory careers to give birth and take care of children and elderly kin. Recent legal changes in land use rights have the potential to encroach on women's equal access to land use, with grave long-term implications for female migrant workers' livelihood security. However, gender bias does not begin to capture the plight of millions of Chinese workers during the reform period. Middle-aged workers in the state sector, whether male or female, confront age discrimination, and migrant workers of both genders suffer from their caste-like status of being a rural resident. Unpaid wages and pensions will continue to plague the lives of both men and women in the working class, for as long as the legal system and the government fail to enforce the Labour Law.
Keywords: 330